TEACHING THE MEANING OF SHARING TO THE STUDENTS OF MIFTAHUL JANNAH ORPHANAGE IN THE HOLY MONTH OF RAMADAN TO ACHIEVE BLESSINGS AND REWARDS - Rico Nur Ilham; Muttaqien; Fuadi; Yunina; Amru Usman; Rusydi Abubakar (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2025)
This study aims to explore and understand the method of teaching the meaning of sharing to students at the Miftahul Jannah Orphanage during the month of Ramadan. The study used a qualitative approach with a case study method. Data were collected through observation, interviews, and documentation of sharing activities carried out by students and caregivers. The results of the study showed that the direct experience approach through sharing practice activities was more effective in fostering empathy, sincerity, and social sensitivity. However, there are still obstacles in understanding the meaning of sharing and limited resources. With religious guidance and role models from caregivers, sharing activities can shape the social and spiritual character of students. This study concludes that teaching sharing that is carried out directly, supported by religious practice and guidance, is effective in shaping the social and spiritual character of students, so that this model can be used as a reference for developing similar programs.